Improvement of the methodology of the tetrazolium test using different pretreatments in seeds of the genus Epidendrum (Orchidaceae) (2020)
The aim of the present study was to determine the most suitable pretreatment to enhance the tetrazolium test in seeds of the Epidendrum genus. Initially, mature capsules were harvested at El Escorial village, in the municipality of Pamplona, ​​Colombia. Subsequently, the seeds were subjected to five pretreatments: deionized water, 0.5% NaClO, 1.0% NaClO, 10.0% sucrose and a control group. Using the syringe method with cloth filter, the seeds were rinsed with distilled water and subjected to two concentrations of tetrazolium solution (0.25%, 1.0%) and three exposure times (6 h, 24 h and 48 h). Finally, the tetrazolium viability test results were correlated with the in vitro germination test. It was found that the use of deionized water improves the efficiency of the tetrazolium test in seeds of Epidendrum fimbriatum and E. microtum; as in seeds of E. elongatum when using 1.0% tetrazolium for 24 h. Similarly, a high correlation was found between viability and germination, using deionized water and 10.0% sucrose, with homogeneous results with each other